Integrated stratigraphy and clay mineralogy of the Owadów–Brzezinki section (Lower–Upper Tithonian transition, central Poland): implications for correlations between the Boreal and the Tethyan domains and palaeoclimate. Issue 2 (2023) - Błażejowski, Błażej; Pszczółkowski, Andrzej; Grabowski, Jacek; HubertWierzbowski, HubertWierzbowski; Deconinck, Jean-Francois; Olempska, Ewa; Teodorski, Artur; Nawrocki, Jerzy
No abstract available